Elucidation of thermal degradation kinetics of Labisia pumila’s polyphenols - Gimbun, Jolius (2016)
Labisia pumila (Kacip fatimah), contains many useful polyphenols leading to various activities such as pre and post-menopausal issues as well as effective for controlling obesity due to the presence of phytochemical profiles (e.g. phenolics, flavonoids and resorcinols) in the extracts. Processing stage of L. pumila, often involves high temperature causing bioactive compounds degradation. The kinetics of polyphenols degradation is not understood and this is the aim of this work. Polyphenols degradation at various temperature and time exposure was quantified via UPLC, and then degradation kinetics was evaluated using both the reaction and Arrhenius approach. Standards gallic acid, protocatechuic acid and epigallocatechin produced single, double and triple degradation rate constant (k) values, respectively with second-order rate law indicating the existence of a multistage degradation. Among all the target compounds studied, epigallocatechin was found to be the most sensitive to thermal degradation with the shortest half-life of 4.78 min. In the case of mixed polyphenols of L. pumila extracts, no distinctive degradation kinetics was found due to simultaneous synthesis and degradation of polyphenols as the heating experiment is performed.